New Generalized Algorithm for Developing k-Step Higher Derivative Block Methods for Solving Higher Order Ordinary Differential Equations - Oluwaseun Adeyeye; Zurni Omar (Institute for Research and Community Services (LPPM) ITB, 2018)
This article presents a new generalized algorithm for developing k-step (m+1)th derivative block methods for solving mth order ordinary differential equations. This new algorithm utilizes the concept from the conventional Taylor series approach of developing linear multistep methods. Certain examples are shown to show the simplicity involved in the usage of this new generalized algorithm.